Healthcare Leadership with Political Astuteness and its role in the implementation of major system change: the HeLPA qualitative study - Justin Waring; Simon Bishop; Jenelle Clarke; Mark Exworthy; Naomi J Fulop; Jean Hartley; Angus IG Ramsay; Georgia Black; Bridget Roe (NIHR Journals Library, 2022)
Background: The implementation of change in health and care services is often complicated by the 'micropolitics' of the care system. There is growing recognition that health and care leaders need to develop and use types of 'political skill' or 'political astuteness' to understand and manage the micropolitics of change. Aim: The aim of this study was to produce a new empirical and theoretical understanding of the acquisition, use and contribution of leadership with 'political astuteness', especially in the implementation of major system change, from which to inform the co-design of training, development and recruitment resources. Methods: The qualitative study comprised four work packages. Work package 1 involved two systematic literature reviews: one 'review of reviews' on the concept of political astuteness and another applying the learning from this to the health services research literature. Work package 2 involved biographical narrative interviews with 66 health and care leaders to investigate their experiences of acquiring and using political skills in the implementation of change. Work package 3 involved in-depth qualitative case study research with nine project teams drawn from three regional Sustainability and Transformation Partnerships operating in different English regions. Work package 4 involved a series of co-design workshops to develop learning materials and resources to support service leaders' acquisition and use of political skills and astuteness. Results: The concepts of political skills and astuteness have had growing influence on health services research, yet these have tended to emphasise a relatively individualised and behavioural view of change leadership. The interview study suggests that, although leaders certainly use individual skills and behaviours when implementing change, change processes are contingent on local contextual factors and the patterns of collective action in the forms of interlocking constellations of political interactions. The in-depth case study research further shows these interactive, contingent and collective processes in the implementation of major system change. The study finds that major system change occurs over several linked stages, each involving particular controversies for which skills, strategies and actions are needed. Informed by these findings, and through a series of co-design workshops, the study has produced a set of resources and materials and a workbook to support individuals and project teams to acquire and develop political skill. Limitations: The study was complicated by the COVID-19 pandemic and there were difficulties in recruiting in-depth cases for observational research, and also recruiting patient and community groups. Conclusions: Health and care leaders can develop and use a range of skills, strategies and actions to understand and navigate the diverse interests that complicate change. Building on the literature, the study presents a novel empirical framework of these skills, strategies and behaviours, and shows how they are used in the implementation of major system change. This study concludes with a set of co-designed learning resources and materials to support future leaders to develop similar skills and strategies. Further evidence is needed on the contribution of the learning resources on leadership activities and to understand the contribution of political skills to other areas of service governance. Study registration: This study is registered as researchregistery4020. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 11. See the NIHR Journals Library website for further project information.